Final crisis - Morrison, Grant (DC Comics, 2014)
"What happens when evil wins? That's the question Superman, Batman, the Justice League and every being in the DCU have to face when Darkseid and his otherworldly legion of narcissistic followers actually win the war between light and dark. Featuring the deaths and resurrections of major DC characters, FINAL CRISIS is more than your average multi-part event-it's a deconstruction of Super Hero comics and a challenging, thought-provoking take on the modern, four-color icons"-- Provided by publisher.